2017
DOI: 10.5897/ajbm2017.8407
|View full text |Cite
|
Sign up to set email alerts
|

Fair value accounting and earnings quality (EQ) in banking sector: Evidence from Europe

Abstract: This research investigates the influence of fair value accounting (FVA) on earnings quality (EQ) inEuropean banking sector over the 2007 to 2016 period. As financial reporting system of banks is particularly exposed to FVA, we assume that FVA may produce significant effects on EQ for European banks. It can be expected that financial instruments' prices are not available in illiquid markets, so Fair Values are estimated by applying valuation models. The application of valuation models (that is, market to model)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The definitions of these components were discussed earlier and are presented in Table 1. According to the definitions of the four components (with a reference to Paoloni et al, 2017), high values of PERS (better sustainability), and low values of PRED (smaller error in earnings predictions), VAR (low volatility) and SMOOTH (effective smoothing activities) refer to better quality of earnings. After calculating the raw values of the components for each bank, rankings of all 128 banks in the sample were created by each component, by giving the highest rank (that is, 128) for the bank showing the best value from the viewpoint of earnings quality, and giving the lowest rank (that is, 1) for the worst value.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The definitions of these components were discussed earlier and are presented in Table 1. According to the definitions of the four components (with a reference to Paoloni et al, 2017), high values of PERS (better sustainability), and low values of PRED (smaller error in earnings predictions), VAR (low volatility) and SMOOTH (effective smoothing activities) refer to better quality of earnings. After calculating the raw values of the components for each bank, rankings of all 128 banks in the sample were created by each component, by giving the highest rank (that is, 128) for the bank showing the best value from the viewpoint of earnings quality, and giving the lowest rank (that is, 1) for the worst value.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most recent studies in this field is that of Paoloni et al (2017), who argue that, from the seven factors defined by Francis et al (2004), the three market-based components have lower relevance in measuring earnings quality, as they are derived from market data that change quickly and are often uncertain. Therefore, they only use the four accounting-based components, namely persistence (PERS), predictability (PRED), volatility (VAR) and smoothing (SMOOTH) of earnings for computing EQ.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary other studies reported that fair value has increased earnings quality (Takacs et al, 2020;Yao et al, 2018;Paoloni, 2017). The advocates of fair value believe that, since fair value reflects the current price of a security which is the starting point for the forecasting of future price, it is assumed that fair value has greater predictive power as compared to the historical cost model.…”
Section: Fair Value Accounting and Earnings Qualitymentioning
confidence: 98%
“…This study, which follows earlier empirical researchers (e.g. Francis et al, 2004;Sodan, 2015;Paoloni et al, 2017), adopts earnings quality as a multidimensional concept and investigates the impact of FV gains/losses on the four most popular EQ accounting measures-persistency, predictability, volatility, and smoothing-in an aggregate form.…”
Section: Introductionmentioning
confidence: 99%